EFFECT OF FREE-FLOATING PLANTS ON WEED EMERGENCE, GROWTH, AND YIELD OF TRANSPLANTED AMAN RICE VARIETIES: Effect of floating plants on weed management of rice - WAHID, TANVIR; ALI, HAZRAT; MASUD, ABDULLAH AL; MALEK, MOHAMMAD; MASUM, SHEIKH MUHAMMAD (Innovare Journal of Agricultural Sciences, 2023)
At Sher-e-Bangla Agricultural University’s agronomy field in Dhaka, Bangladesh, a study was carried out from July to December 2019 to determine the suppressing capacity of floating weeds in T. aman rice (Oryza sativa L.). The experiment consisted of two factors, namely, rice varieties (three), including Tulshimala, BR11(Mukta), and Bangladesh Rice Research Institute (BRRI) hybrid dhan6, and weed management (five), including weedy check (control), integrated weed management (IWM) (Pretilachlor 6% + pyrazosulfuron 0.15% and one hand weeding), spreading of Pistia stratiotes, Lemna minor, and Salvinia molesta in 0.5 m2 area in a split-plot design with three replications. The ranking of the relative rate of spreading over the experiment was L. minor > S. molesta > P. stratiotes. A total of six weed species representing five families were found from the transplanting to the later stage of rice growth, where the occurrence of weed infestation related to rice variety and crop growth. BRRI hybrid dhan6 significantly suppressed weeds in related plots. Although weed biomass was significantly reduced, the morphological and biomass characteristics of T. aman rice varieties got disadvantages when grown with P. stratiotes and S. molesta. Cultivation of BRRI hybrid dhan6 and weed control through IWM gave the highest grain yield (5.92 t ha-1). However, the spreading of L. minor facilitated optimal weed control, and good yields were harvested without significant differences, irrespective of varieties. Therefore, competitive weed variety should be considered along with the spreading of L. minor to reduce herbicide loads in the environment and to the evolution of cross-resistant weed populations.